2020
DOI: 10.1590/1517-869220202602218943
|View full text |Cite
|
Sign up to set email alerts
|

Does Pre-Competitive Anxiety Interfere in the Performance of Boxing Athletes in Brazil? A Pilot Study

Abstract: Introduction: Pre-competitive anxiety is one of the psychological factors that can greatly influence athletes' performance, especially when it comes to individual sport like boxing. Objective: To analyze the level of pre-competitive anxiety in male athletes in the adult and young adult categories, and their correlation with the final results of the last Brazilian National Championship. Methods: A total of 60 young adult athletes participated in the study: 38 non-medalists (17.17±0.54 years and 66.38±13.21 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
1
0
3
Order By: Relevance
“…Similarly, the duration of competitive engagement displayed a moderate negative correlation with anxieties and showed no correlation with self-confidence. Thus, this outcome partially confirms the study's first hypothesis, as it was anticipated that the years of practice would decrease athletes' levels of competitive anxiety (Alejo et al, 2020;Jordet, 2017). In fact, according to Jordet (2017), an athlete's experience is the best predictor of cognitive anxiety, meaning that more experienced competitors tend to exhibit lower anxiety levels.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, the duration of competitive engagement displayed a moderate negative correlation with anxieties and showed no correlation with self-confidence. Thus, this outcome partially confirms the study's first hypothesis, as it was anticipated that the years of practice would decrease athletes' levels of competitive anxiety (Alejo et al, 2020;Jordet, 2017). In fact, according to Jordet (2017), an athlete's experience is the best predictor of cognitive anxiety, meaning that more experienced competitors tend to exhibit lower anxiety levels.…”
Section: Discussionsupporting
confidence: 77%
“…Las variables que mide el cuestionario suelen ser fluctuantes en función tanto de la experiencia y habilidades psicológicas del deportista, como por el proceso de la preparación que ha realizado para esa competición específica y la relevancia que esta tenga para el deportista (Piskorska et al, 2016). El boxeo, es un deporte de alto riesgo con una gran carga emocional durante cada competición, a la que se suma la posibilidad de no seguir avanzando en el campeonato si se pierde una sola pelea; sin embargo, los resultados de nuestro estudio sugieren que los boxeadores percibían niveles de ansiedad somática y cognitiva moderados, mientras que en el caso de la autoconfianza eran elevados, lo que sugiere que existe una buena preparación del deportista y un adecuado manejo de la ansiedad precompetitiva (Alejo et al, 2020;Piskorska et al, 2016).…”
Section: Porunclassified
“…En México, así como en el estado de Sinaloa, los deportes de combate forman parte de los deportes individuales con mayor popularidad, siendo el boxeo uno de los que más apasionan al público y atrae la atención de niños y jóvenes para practicarlo. El boxeo es un deporte que promueve una práctica segura para el aprendizaje de cualidades como la disciplina, respeto y defensa personal en los jóvenes (Panchal & Kumar, 2016); sin embargo, para llevarlo a cabo a nivel competitivo y hacia el alto rendimiento requiere de una gran dedicación, ya que los deportistas además de su preparación física, técnica y mental deben someterse a continuos regímenes alimenticios restringidos para mantenerse en un peso según su categoría (Alejo et al, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…A study conducted by Alejo et al (2020) shows that anxiety before competition is one of the psychological factors that can significantly affect athlete performance, especially in individual sports such as boxing. The research results conducted by Bisa (2020) showed that psychological factors in the form of anxiety affect both directly and indirectly the peak performance of a boxer.…”
Section: Introductionmentioning
confidence: 99%